$(2, 3)$-GENERATION OF THE GROUPS $PSL_5(q)$ (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2005)
We prove that the group $PSL_{5}(q)$ is $(2, 3)$-generated for any $q$.